From industrial forestry to natural resources management - lessons learnt in forestry assistance - Persson, R. (SIDA. Department for Natural Resources and the Environment, 1998)
The report summarises some Swedish experiences in assistance to forestry. Sweden's development from forestry mining in the last century to sustainable forestry is discussed as is the impact of assistance to Swedish forestry during 150 years. Forestry assistance has gone through a number of phases (Industrial forestry, Social forestry, 'Environmental' forestry and Sustainable management of renewable natural resources). The report does not detail the forestry problems giving cause for assistance in developing countries but concentrates on analysing the role of donor organisations. There are too many problems in the administrative system and improved forestry assistance requires changes in the donor-organisations.